Optimum Location Analysis of Story Isolation System on High Rise Building - Alif Muhammad Reza; Herlien D. Setio (Institut Teknologi Bandung, 2021)
Abstract Various studies have been carried out to evaluate the feasibility and effectiveness of the story isolation system. The results obtained are also quite impressive, where the story isolation system gave a better story drift reduction than the base isolation system. However, these studies only focused on low-rise buildings, even though the story isolation system will be more engaging if it could also be compatible with high-rise buildings. In this study, a numerical analysis will be carried out on 30-, 40-, 50-, and 60-story buildings to evaluate the story isolator’s location, so that the system gives an optimum reduction of story drift and story shear. Then a general solution is sought to become a reference for buildings with different plans and heights. Keywords: Story isolation system, story isolator optimum location, high-rise building. Abstract Berbagai penelitian telah dilakukan untuk mengevaluasi kelayakan dan efektivitas sistem isolasi tingkat. Hasil yang diperoleh juga cukup mengesankan, dimana sistem isolasi tingkat memberikan reduksi simpangan antar tingkat yang lebih baik dibandingkan dengan sistem isolasi dasar. Namun, studi tersebut hanya berfokus pada bangunan bertingkat rendah, padahal sistem isolasi lantai akan lebih menarik jika dapat juga digunakan pada bangunan bertingkat tinggi. Dalam studi ini, analisis numerik akan dilakukan pada bangunan berlantai 30, 40, 50, dan 60 untuk mengevaluasi lokasi isolator tingkat yang memberikan reduksi simpangan tingkat dan geser tingkat terbesar. Kemudian dicari solusi umum untuk menjadi acuan untuk bangunan dengan denah dan ketinggian yang berbeda. Kata kunci: Sistem isolasi tingkat, lokasi optimum isolator tingkat, bangunan bertingkat tinggi.